Singaporean men and marriage. - Ko, Chong Tat. (2013)
Late marriage and the increasing trend of singlehood are two of the main factors attributed to low fertility in Singapore. Singapore is experiencing some form of marriage squeeze between the highly educated women and less educated men since most marriages are hypergamous. Increasingly, there are more women pursuing university qualifications; this may reduce the pool of potential spouses for these men.